Roundabout practices - Pochowski, Alek; Paul, Andy; Rodegerdts, Lee A. 1970- (Synthesis of highway practice ;, 2016)
As of 2013, there were an estimated 3,200 roundabouts in use throughout the country. This synthesis documents and summarizes roundabout policies, guidance, and practices in place within state departments of transportation (DOTs) as of 2015. The primary focus of the synthesis is on roundabout selection and design with a secondary focus on performance analysis. Information used in this study was gathered through a literature review and a survey of state DOTs. Personnel from seven states were interviewed to create case examples and more specific information. Among the findings, the primary reason cited for the selection of roundabouts is improved safety performance compared with other intersection options, followed by shorter vehicular delays and higher capacity. Planning-level cost estimates (screening or feasibility level estimates) for mini-, single-lane, and multilane roundabouts ranged from $249,000 to $2.05 million. The majority of reporting states have developed some public education materials to support roundabout projects, such as websites, videos, and flyers and/or pamphlets. To analyze roundabout performance, about three-quarters of the reporting states use some form of the Highway Capacity Manual 2010 model and SIDRA's Standard Model. Most of the reporting states analyze safety performance at roundabouts, using crash modification factors, crash reduction factors, and/or the Highway Safety Manual predictive methodology. Most states use a design life of 20 years when developing the ultimate roundabout design. However, the majority uses a phased implementation approach.